Dual-career couples: Specific challenges for work-life integration. - Abele, Andrea E.; Volmer, Judith (Creating Balance?! International perspectives on the work-life integration of professionals., 2011)
Presents an overview of issues regarding dual-career couples (DCCs). After a brief introduction to the development of DCCs and the frequency of DCCs in Europe and the United States, theoretical models that aim to explain why couples live in relationships in which both partners work are outlined. In addition, the potential advantages and disadvantages of this type of relationship are discussed. Then, empirical findings on the relationship between DCCs and stress, well-being, partnership issues, career and mobility issues, parenthood issues, and gender-related issues. Thereafter, strategies to promote work-life integration of DCCs are discussed. These strategies are aimed to assist integration on the individual, partnership, and organizational levels. It is concluded that compatibility management strategies, societal support, and organizational strategies are necessary for successful work-life integration.
Keywords: Dual Careers; Family Work Relationship; Family Structure; Couples; Relationship Satisfaction; Stress; Occupational Mobility; Social Support; Strategies